Analysis of the Utilization of E-bookcases as Learning Resources Reference: Analisis Pemanfaatan E-bookcase sebagai Referensi Sumber Pembelajaran - Marifah, Ainun; Kurniawan, Machful Indra (Indonesian Journal of Education Methods Development, 2022)
This research is an analysis research on the use of E-bookcase as a reference for learning resources. The purpose of this study is to find out how to use E-bookcase in online learning as a reference for learning resources and the obstacles encountered when using E-bookcase. This study uses descriptive qualitative research methods. The result of this research is the use of this E-bookcase is carried out during online learning. The teacher gives the E-bookcase link to students through the class WhatsApp group, then the link is opened during the zoom. The features in this application are also diverse and the appearance is very attractive so that it increases learning motivation and student grades even though it is only 1 point. The use of this E-bookcase increases student references and increases knowledge. In the use of this E-bookcase the obstacles encountered are not so many. There are only a few students who still do not understand the use of E-bookcases and the internet network is less stable to use E-bookcases.